The brains of elite soccer players are subject to experience-dependent alterations in white matter connectivity - Yao, Z. F.; Sligte, I. G.; Moreau, D.; Hsieh, S.; Yang, C. T.; Ridderinkhof, R.; Muggleton, N. G.; Wang, C. H. (Cortex, 2020)
Soccer is the only major sport with voluntary unprotected head-to-ball contact. It is crucial to determine if head impact through long-term soccer training is manifested in brain structure and connectivity, and whether such alterations are due to sustained training per se. Using diffusion tensor imaging, we documented a comprehensive view of soccer players` brains in a sample of twenty-five right-handed male elite soccer players aged from 18 to 22 years and twenty-five non-athletic controls aged 19-24 years. Importantly, none had recalled a history of concussion. We performed a whole-brain tract-based spatial statistical analysis, and a tract-specific probabilistic tractography method to measure the differences of white matter properties between groups. Whole-brain integrity analysis showed stronger microstructural integrity within the corpus callosum tract in soccer players compared to controls. Further, tract-specific probabilistic tractography revealed that the anterior part of corpus callosum may be the brain structure most relevant to training experience, which may put into perspective prior evidence showing corpus callosum alteration in retired or concussed athletes practicing contact sports. Intriguingly, experience-related alterations showed left hemispheric lateralization of potential early signs of concussion-like effects. In sum, we concluded that the observed gains and losses may be due to a consequence of engagement in protracted soccer training that incurs prognostic hallmarks associated with minor injury-induced neural inflammation.